ISSUES OF PROTECTION OF THE RIGHTS OF BUSINESS SUBJECTS IN THE LEGISLATION ON FACTORING (TRANSFERS OF LIABILITIES) - Sukhodolska, Anastasiya (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose: to research regulations and standards at the level of both national and international law, theoretical-legal, ethical, and moral principles of factoring agreements and court practice. The methodological basis of the research consists of comparative legal methods, special legal methods, synthesis and generalization, observation, general scientific methods of analysis. Results: based on a full and comprehensive study of the problems of implementing the rules in the field of protection of the rights of business entities in factoring legislation, to develop systematic conclusions and proposals that determine the ways to improve the functioning of the legal mechanism in this area of economic relations in order to determine the principles and conditions for the State to comply with the basic constitutional guarantees and international treaties ratified by the Parliament of Ukraine, as well as the powers of the executive authorities that regulate these relations in Ukraine. Discussion: the author establishes that the issue of protection of business entities’ rights in the Ukrainian legislation on factoring requires regulation in the market of economic services and further adaptation to the EU law, comprehensive analysis of legislation and study of the practice of its implementation and judicial protection, as well as development of a single mechanism for protection of contracting parties based on the principles of equality, fairness, good faith and not contrary to the public interest. As a result, in order to find ways to overcome the economic crisis caused by Russian aggression and ensure the country’s sustainable development, it became necessary to analyze the current legislation and determine the need for novelization of legal regulation, changes in the regulation of rules and procedures in the field of economic relations, including factoring agreements.